PLOT IN JUSTIN LIN'S THE FATE OF THE FURIOUS - Kardari, Lisna Dewi; Suarniti, Gusti Ayu Made Rai; Kertiasih, Ni Nyoman (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2023)
The research, titled "Plot in Justin Lin’s The Fate of The Furious," aims to explore how the plot is developed in the movie "The Fate of The Furious" directed by Justin Lin and identify the components of the plot structure present in the film. The study utilizes Freytag's plot methods (1863) as its theoretical framework. The research methodology involves determining the data sources, collecting data, and analyzing the data based on Freytag's methods. The data are classified according to these methods, and calculations are conducted to understand the presence and elements of the plot in "The Fate of The Furious." The theoretical foundation for analyzing the plot methods comprises the five steps outlined by Freytag in his book "An Exposition of Dramatic Composition and Art." This theoretical framework is applied to scrutinize the movie, considering both the dialogue and each scene. The findings reveal five essential steps in the plot structure: exposition, rising action, climax, falling action, and denouement. These plot elements serve as a narrative framework for "The Fate of The Furious," shaping the events, conflicts, and resolutions that unfold throughout the film.